Students’ Relational Thinking and Mathematical Communication in Contextual Problem-Solving in Muhammadiyah Junior High School 8 Batu - Aulia, Syafirda Azmi; Cholily, Yus Mochamad; Ummah, Siti Khoiruli; Mustakim, Siti Salina (Jurnal Pendidikan Progresif, 2024)
Abstract: Students' Relational Thinking and Mathematical Communication in Contextual Problem-Solving in Muhammadiyah Junior High School 8 Batu Objective: This research aims to describe students' relational thinking and mathematical communication processes in solving mathematical problems using contextual problems in curved geometric shapes. Method: This research uses qualitative research methods by collecting data using relational thinking tests, written mathematical communication, and interviews to determine oral mathematical communication. The research instruments used in this research were relational thinking tests, written mathematical communication, and interview guidelines. The subjects of this research were junior high school students in the IX class. The data analysis is a test and interview results, then conclusions are drawn. Findings: The research results show that the dominant students were in the medium category after carrying out tests on relational thinking and written mathematical communication. Conclusion: In the analysis of oral communication thinking, the results showed that students who were in the low category in relational thinking processes were still unable to fulfill several indicators; apart from that, students were still not able to communicate mathematically, but in mathematical oral communication they were in the medium category. Meanwhile, students in the moderate category of relational thinking processes can only fulfill several indicators and must be able to communicate mathematically. Still, according to the analysis of mathematical oral communication, they are classified as good. Students in the high category of relational thinking processes are just unable to build complete relationships and can communicate mathematically well. Keywords: relational thinking, mathematical communication, contextual problems.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202442